CULTURAL CARE THEORY BASED ON THE BARBARA BARNUN'S POINT OF VIEW - Lorena Barbosa Ximenes; Luiza Jane Eyre Xavier de Souza; Lorita Marlena Freitag Pagliuca (Universidade Federal do Paraná, 1999)
Nursing has been trying to base its professional practice in theories; authors have been proposing analysis models that allow to evaluate theory's application to specific situations. Therefore, this study has the purpose to analyze, in a reflexive way, Leininger's cultural care theory used in an empiric research. The choice of a Monticelli's (1997) work called Birth as a ritual passage: approach for the care to women and newly born and a review of cultural care theory were chose to identify the congruence between Leininger's theory and the framework that was set up by Monticelli. To pursue the aim, it was opted to use Barnun's guidelines with subjects which are related to theory's main principles; the relationship among its elements; the kind of theory and how nursing has been inserted within the assumptions. It was possible to verify that a cultural care theory has an epistemological accuracy with Barnun's analysis principles and it provides conditions for being implemented in nursing practice, as the Monticelli's works can show. It is verified, the viability of describing how the nurse should act in its practice proposing that a cultural care method can be implemented for human beings. It is concluded that the nursing practice can be based in theoretical, philosophical and methodological frameworks and they contribute to conquest the professional autonomy.